Getting Shut Out of the International Capital Markets : It Doesn't Take Much - Marion, Nancy (IMF Working Papers; Working Paper ;, 2006)
We use a simple model of international lending to show that an emerging market borrower who might default can be shut out of international capital markets without warning. A modest haircut on obligations, for example, can shut down lending.